FORMATION OF INTELLECTUAL CORPORATE CAPITAL: METHODS AND MODERN TRENDS - Kalenyuk I.,; Grishnova E.,; Tsymbal L.,; Djakona A.,; Panchenko E., (Scientific Journal of Pedagogy and Economics, 2020)
The accumulated assets of intellectual capital serve as the basis for the formation of competitive advantages of TNCs in the global economy. The world leading corporations are diversifying methods of forming and attracting intellectual capital in terms of increased competition. The aim of the study is to identify modern features and methods of intellectual capital accumulation as the basis of competitive advantages of TNCs in the global environment. The findings imply that the basis of leadership and high competitiveness of TNCs are the accumulated assets of intellectual capital. The result of the study was the systematization and disclosure of the methods of accumulation of intellectual corporate capital. The current trends in the accumulation of intellectual capital assets by leading TNCs of the world are revealed. The accumulation of corporate intellectual capital of corporations is carried out on the basis of large-scale investment in assets: the development of corporate forms of personnel training, a tremendous increase in R&D expenses, the formation of distributed innovation networks and open innovation platforms, the introduction of the latest knowledge management mechanisms. The forms of attracting intellectual capital from outside are actively used: the search and attraction of talented and highly qualified human resources from other countries, the purchase of patents, technologies, management models, mergers and acquisitions of companies, etc. Transnational corporations are becoming the leading subjects of spending on science in the world: in the top ten countries they account for more than half of all R&D costs, and in the leading countries of the USA and China - up to 80%. The accumulation of corporate intellectual capital is characterized by tendencies in the formation of two powerful world leaders - the USA and China, increased competition, a sharp increase in R&D costs, regional and industry transformations. The world leaders in science spending are the corporate sector in the United States and China. The sectoral structure of the world's leading transnational corporations is changing: instead of oil and automobile, the top ten transnational corporations now mainly include computer and high-tech companies. Aggressive strategies for increasing intellectual assets are being implemented. An effective tool for accumulating intellectual assets is mergers and acquisitions. The leaders in the number of mergers and acquisitions are TNCs from leading countries: USA, China, United Kingdom, Germany and Japan. The formation of corporate intellectual capital is an important step in building an effective synergistic interaction of all the constituent triangles “business-education-science”. This triad is a key tool for the strategic development of the knowledge economy for any country in the world.